An assessment of the potential fungal bioaerosol production from an active living wall. (January 2017) - Irga, P.J.; Abdo, P.; Zavattaro, M.; Torpy, F.R.
Abstract: Active living walls, or indoor air biofilters, have been proposed as a sustainable and aesthetic means of improving indoor air quality. However these systems have yet to be adequately assessed for their potential contribution to airborne fungal proliferation in indoor spaces. The current work represents a simulation study to determine, under realistic office conditions, whether a typical active living wall makes a quantifiable contribution to the airborne aeromycota. We found that the living wall studied made no significant contribution to the density or diversity of airborne culturable fungi in a test room. Few organisms of concern to public health were identified. We conclude that active biofilters are unlikely to make hazardous contributions to indoor fungi; however, further work that documents the bioaerosol generation rate with variations in temperature, airflow, plant varieties, planting densities, maintenance schedule, age of plants, plant growth substrates and substrate moisture content need further elucidation. Highlights: An active living wall system was tested for its potential fungal bioaerosol production. The effect on ambient indoor physiochemical air parameters was also tested. No substantial contributions to the density or diversity of bioaerosols was observed.